Rewriting Scripture in Second Temple Times, Sidnie White Crawford : book review - Naudé, Jacobus A. (Old Testament essays, 2008)
Sidnie White Crawford is professor of Hebrew Bible and chair of the Classics and Religious Studies Department at the University of Nebraska-Lincoln. She is also past president of the W. F. Albright Institute of Archaeological Research in Jerusalem. She is one of the younger generation of Dead Sea Scroll scholars privileged to work on the first editions of the manuscripts. Frank Moore Cross invited her in 1986 to edit for her dissertation seven of the Cave 4 Deuteronomy manuscripts assigned to his lot (one of them contains excerpts of a harmonised text of Deuteronomy). In 1989 John Strugnell invited her to take over his work on the manuscripts at the time called Pentateuchal Paraphrases, and Emanuel Tov graciously accepted her as his junior collaborator on the project.